2017
DOI: 10.1016/j.rbmo.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Semen quality and alcohol intake: a systematic review and meta-analysis

Abstract: Alcohol consumption is widespread in the Western world. Some studies have suggested a negative association between alcohol intake and semen quality although others have not confirmed this. MEDLINE and Embase were searched using 'alcohol intake' OR 'alcohol consumption' OR 'alcohol drinking' OR 'lifestyle' combined with 'semen quality' OR 'sperm quality' OR 'sperm volume' OR 'sperm concentration' OR 'sperm motility' for full-length observational articles, published in English. Reference lists of retrieved artic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
90
3
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 170 publications
(100 citation statements)
references
References 23 publications
3
90
3
4
Order By: Relevance
“…Also, we did not find any association between alcohol consumption and semen quality which was again in line with the CHAPS study (Povey et al 2012;Pacey et al 2014). Discordance with a recent review reported a positive association between excess alcohol intake and semen volume and morphology was noted (Ricci et al 2017). When considering tea intake, our result was in line with a recent meta-analysis which showed that caffeine intake (including tea and caffeinated beverages) did not show a clear association with semen parameters (Salas-Huetos et al 2017).…”
Section: Discussionsupporting
confidence: 83%
“…Also, we did not find any association between alcohol consumption and semen quality which was again in line with the CHAPS study (Povey et al 2012;Pacey et al 2014). Discordance with a recent review reported a positive association between excess alcohol intake and semen volume and morphology was noted (Ricci et al 2017). When considering tea intake, our result was in line with a recent meta-analysis which showed that caffeine intake (including tea and caffeinated beverages) did not show a clear association with semen parameters (Salas-Huetos et al 2017).…”
Section: Discussionsupporting
confidence: 83%
“…A negative association between alcohol intake and semen quality has been suggested by some authors (Martini et al, 2004;Muthusami & Chinnaswamy, 2005), although other studies did not confirm this finding (L opez Teij on et al, 2007;Hansen et al, 2012). According to a recent meta-analysis of 15 cross-sectional studies, occasional consumption does not adversely affect semen variables, whereas a negative association with semen volume and normal morphology emerged for daily consumption (Ricci et al, 2017). However, these findings could not be controlled for confounders such as smoking and age.…”
Section: Introductionmentioning
confidence: 92%
“…It is important to take confounders into consideration since previous studies have shown that a diversity of conditions and factors, such as smoking, alcohol use, age, and BMI also influence sperm parameters, which is in line with the induction of excessive oxidative stress. [ 26–29 ] Although, less research is performed on paternal influences on pregnancy outcomes, we assume that the same confounding factors should be considered.…”
Section: Resultsmentioning
confidence: 99%